IMPLEMENTASI INTEGRATED MARKETING COMMUNICATION (IMC) DALAM MENUNJANG PEMASARAN RUMAH SAKIT DIRGAHAYU SAMARINDA - Wijayanti, Via Violeta Kintan; Daryana, Aditiya Pratama (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Marketing is a function that is very much needed in a company in introducing products or services to consumers, with the aim of achieving profitable sales for the company. This can be done by building strong relationships for product or service users by providing satisfaction. So this can give the company an image of goods or services and can attract consumer subscriptions. Hospital marketing strategies are very important to attract consumers to use products and services. This era of development is very influential for choosing the correct strategy. Due to the current era, most hospitals have become socio-economic institutions. In connection with government policy, there are more and more hospitals in Indonesia, where the increasing number of hospitals means that each hospital competes with each other with its own advantages to get customers. Therefore, good hospital marketing will help hospitals to survive and compete and even develop. Choosing an Integrated Marketing Communication (IMC) strategy can support hospital marketing. Integrated Marketing Communication (IMC) has great potential in influencing performance progress in business, this really gives hospitals a competitive advantage, in increasing brand equity of the hospital's image and ensuring consistency and effectiveness of communication for marketing purposes. This strategy plays a very important role in informing or introducing the hospital to the surrounding community.